Integrated weed management in rainy-season groundnut (Arachis hypogaea) - PATRA, A K; NAYAK, B C (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during rainy (kharij) season of 1997 and 1998 to study the different weed-management practices on groundnut (Arachis hypogaea L.). Pre-emergent application of Alachlor @ 2 kg ai/ha or Fluchloralin @ 1.0 kg ai/ha or Pendimethalin @ 1.0 kg ai/ha, followed by post-emergent application of Fluchloralin @ 1.0 kg ai/ha 1 day after interculture at 20 days after sowing increased pod yield 94.1,89.3 and 88.0% respectively over the unweeded control (810 kg /ha). The respective net monetary returns were Rs 7 916, Rs 8 528 and Rs 8 341/ha compared with Rs 770 with un weeded control and Rs 5 467 with farmers' practice of hoeing and weeding at 20 days after sowing. Integrated weed management involving pre-emergent application of Alachlor @ 2 kg ai/ha at 1 day after sowing, followed by post-emergent application of Fluchloralin @ 1 kg a i/ha at 1 day after interculture recorded higher weed control efficiency (87.9%).